Argestes angolaensis sp. nov. (Copepoda: Harpacticoida: Argestidae) from theAngola Basin (Southeast Atlantic), and the phylogenetic characterization of thetaxon Argestes Sars, including the redescription of A. mollis Sars, 1910, and A.reductus (Itô, 1983) - George, Kai Horst (Zootaxa, 2008)
Argestes angolaensis sp. nov. (Copepoda, Argestidae) is described from the Angola Basin. Detailed comparison with the other Argestes species, A. mollis Sars, 1910 and A. reductus (Itô, 1983), which are redescribed in the present contribution, reveals autapomorphies for the genus, finally enabling the characterization of Argestes as a monophylum: 1) body densely covered with fine small cuticular spinules, 2) sensilla of cephalothorax and free thoracic somites arising from long tubercles, 3) antennula with very strong seta terminally on 6th segment in female (9th–10th in male). This investigation, concentrating on the systematic status of Argestes and first remarks on its relationships to Parargestes Lang, is the first in a series dedicated to the phylogeny of Argestidae Por, 1986.